PSYCHOLOGICAL CHARACTERISTICS OF ADOLESCENCE - Khosimova Dilorom (American Journals, 2023)
This article reflects on the activities of the adolescent period, as well as the peculiarities of the activities of this period and changes in the mental state.
Keywords: adolescence, study, communication, labor, activity.